The contemporaneous relationship between stock prices and monetary policy in Kenya - Wambul, Reuben Muhindi (Strathmore University, 2016)
Movements in the stock market can have a significant impact on the macroeconomy and stock prices are therefore likely to be an important factor in monetary policy decisions. In view of the raging debate on whether central banks should react directly to asset price movements, this paper attempts to measure the contemporaneous response relationship between stock prices and monetary policy in Kenya applying the procedure of Rigobon and Sack (2003) to identify and estimate a VAR in the presence of heteroskedasticity of stock returns. The study finds a significant positive policy response with a 1% percent rise (fall) in the NSE-20 share index, a proxy for stock prices, increasing the likelihood of a 1.97% tightening (easing) of the short-term interest rate which captures monetary policy actions by the CBK.
Keywords: asset prices; stock prices; monetary policy; interest rates; endogeneity